High Frequency of Mutator Strains among Human Uropathogenic Escherichia coli Isolates - Denamur, Erick (American Society for Microbiology, 2002)
By using a panel of 603 commensal and pathogenic Escherichia coli and Shigella isolates, we showed that mutation rates of strains vary considerably among different ecotypes. Uropathogenic strains had the highest frequency of mutators, while strains from patients with bacteremia had the lowest mutation rates. No correlation between the mutation rates and antibiotic resistance was observed among the studied strains.